Developing information literacy programs : Best practices from Latin America, Spain and Portugal (2017)
ABSTRACT: This article summarizes the best practices framework known as ‘75 Lessons Learned from Information Literacy Programs at Ibero-American Universities’, drawn from the study of 301 information literacy experiences in Latin American countries, Spain and Portugal. This research involved analysis of 499 documents and data triangulation with 113 interviews and 135 surveys. This comprehensive framework is a useful Ibero- American guideline for developing new information literacy programs or strengthening existing ones at a worldwide level.